Family Needs on an Inpatient Brain Injury Rehabilitation Unit: A Quantitative Assessment. Issue 4 (July 2018) - Kreutzer, Jeffrey S.; Marwitz, Jennifer H.; Klyce, Daniel W.; Wilder Schaaf, Kathryn P.; Sima, Adam P.; Welch, Abigail M.; Niemeier, Janet P.
Abstract : Objective: To examine the needs of family members in an inpatient setting and factors predicting extent to which needs are perceived as met. Setting: University health system inpatient rehabilitation unit. Participants: Adult survivors of traumatic brain injury and family members ( n = 85). Design: Prospective, cross-sectional. Main Measure: Family Needs Questionnaire-Revised (FNQ-R). Results: Needs related to the Health Information subscale were most frequently rated as met, whereas needs related to the Instrumental Support and Emotional Support subscales were most frequently rated as unmet. Predictors related to the FNQ-R included family income, gender, and ethnicity. For 4 of 6 subscales, white family members were more likely to rate needs as unmet than minority members. For 3 subscales, females were more likely to rate needs as unmet than males. Greater household income was associated with fewer met needs for 2 subscales. Conclusions: The ranking of met and unmet needs in the present study was remarkably similar to previous studies within and outside the United States. Clinicians should not assume that families with relatively higher incomes will experience fewer unmet needs. Through structured assessment, clinicians can reveal perceived needs that might have otherwise been unrecognized and facilitate appropriate supports. Findings provide direction for inpatient program development. Abstract : Supplemental Digital Content is Available in the Text.